National Internet-Based Survey of the Use, Barriers, Reasons and Beliefs of Mind-Body Practices During the Early Months of the COVID-19 Pandemic - Tracy Hellem PhD, RN; Sandra Benavides-Vaello PhD, RN; Ruth Taylor-Piliae PhD, RN, FAHA, FAAN (SAGE Publishing, 2021)
The purpose of this study was to learn about the use, barriers, reasons and beliefs regarding mind-body practices among adults living in the United States during the beginning months of the 2019 novel coronavirus disease (COVID-19) pandemic. An on-line survey was developed following the Checklist for Reporting Results of Internet e-Surveys (CHERRIES) guidelines and using the online survey software program, Qualtrics ® XM , platform. Pilot testing of the survey was conducted for usability and functionality. The final 24-item survey was distributed via email and social media. A total of 338 adults responded to the survey, with 68.8% indicating that they participated in mind-body activities since the start of the pandemic. Physical activity was the most frequently (61.5%, n = 227) used mind-body practice. Further, 2 of the common barriers to engaging in mind-body practices were lack of motivation and wandering mind. Frequently listed reasons for using mind-body practices were to promote health, reduce stress and relaxation. Respondents believed that mind-body practices resulted in less stress. These findings may be applicable for reducing psychological stress related to the pandemic, as the pandemic continues to impact many areas of the United States.